TPACK Learning Model - Rodiatul Mutmainah (Journal of Mandalika Literature, 2025)
Effective integration into instruction and learning is crucial in the fast-changing environment of today’s education. The Technological Pedagogical Content Knowledge (TPACK) model offers a complete framework for understanding how teachers can use technology, pedagogy, and content knowledge can enhance students learning. This study investigates the theoretical foundations of TPACK, its role in addressing issues in technology-based instruction, and its practical applicability in educational context. This study emphasises the importance of TPACK in promoting effective, technology-integrated teaching methods by investigating the intersection of pedagogy, content, and technology.